An empirical study of the perceived threats and safeguards of auditor independence - Ahmed Razman Abdul Latiff (2008)
The purpose of this study is to examine the perception of auditor independence among the various groups of auditors, financial statement preparers and users. It attempts to investigate factors that threaten auditor independence and evaluates factors that safeguard auditor independence.